Planejamento participativo nas aulas de Educação física escolar: significados existentes nesta proposta - Silva, Peterson Amaro da (2020)
This work has the objective discuss the meanings that is existing in a pedagogical proposal at participative planning at physical education at school. This Search pervades by discussions about management democracy at school and the collective construction of politic pedagogyc project and curriculum with different people in your planning and development, by having a teoric reasoning, Paro (2015; 2016a; 2016b), Silva (2012), Thomé (2014), Natividade; Medeiros (2014), Veiga (2009), Saul; Saul (2013), Noffs (2013). Already the physical education present yourself as a curricular component that, over the years, passed by differents educationals contexts. However, arised several studies that made possible differents points of view and approach, like, for example, Darido (1998;2017), and too the curricular component embased by officials documents. The works researched in the annals of three academic events in the area of the Physical Education, are they, Physical Education Teaching Methodology Seminar (Semef), Physical Education Seminar and the Brazilian Congress of Sports Science (Conbrace), having the criterion selection of words “Physical Education At School”, “Participative Planning”, “Poll”, “Knowledge Building” and “Student’s Knowledge” at the academic work titles for your selection, in the way to a integrative revision (SOUZA; SILVA; CARVALHO, 2010), with the objective of identify and discuss the possibilities, potentialities, challenges and difficults that each work selected introduce in the development of a Participative Planning. Lastly, the meanings existing in this pedagogical proposal at the classes of Physical Education at School has in your construction challenges from the involved people with the education at school in participation at decision making, the participation of different people in differents environment that they frequently go. Simultaneously contradiction between possibilities and difficults at PP, existing in democracy education of humanistic character, that stimulates the autonomy from all people involved with the educational context